"Economy of Trust" in Commercial Obstetric Care: Educated Urban Women as Consumers and Patients - Temkina, Anna (Journal of Economic Sociology, 2017)
This article provides insight into the shaping of the position of urban educated women, which is twofold: As reflexive actors and consumers, these women make an informed choice and pay for childbirth services in maternity hospitals; however, as patients, they trust to their “own” reliable obstetrician. I carry out a contemporary sociological discussion on patients’ choices and their limitations under the influence of neoliberalism and the commercialization of medical care, including for childbirth. Research on paid childbirth care in maternity hospitals is based on in-depth interviews with 35 mothers and 14 obstetricians and midwives who work in commercial health care, as well as observation in two hospitals (St. Petersburg 2015). The empirical data give evidence concerning mothers’ perception of childbirth as an extremely risky process wherein guaranties of safety are needed. These mothers choose the paid service due to their lack of trust of free-ofcharge medicine and the abstract social role of professionals. To cover the cost of childbirth, women (parents) calculate their family resources; they consider the expenditure as heavy budget burden, but they perceive it as inevitable for them. To choose and receive reliable service, they collect thorough information about the reputations of maternity hospitals and obstetricians. After her decision is made, the future mother meets with an obstetrician and midwife in person to negotiate the conditions of delivery and draw up a contract; this has the effect of personalizing the relationship. Attitudes toward professionalism are based on information, experience, and affects. Once the professionals have gained her trust, the future mother delegates them control; the issues of payment are mostly reduced to the brackets of medical interactions. However, women do not behave as passive recipients of medical care; rather, they try to be more active in the negotiations. Ultimately, women act as both consumers of medical services and as patients, establishing trust in professionals by purchasing the care. Together, these phenomena work as an “economy of trust”.